Stride: A History of Competitive Women`s Rowing in Britain, 1945-2000 - Taylor, L. J. (Manchester Metropolitan University in collaboration with the River & Rowing Museum, Henley-on-Thames, 2020)
Since the turn of the century, the British women`s rowing team has enjoyed unprecedented success and profile. Yet such success belies a more chequered history of female participation in rowing in this country. This is the first academic study to consider the trajectory of competitive women`s rowing in Britain. It focuses on the period from 1945 to 2000, with particular interest in international competition and the domestic structuresunderpinning athletes` engagement withit. It addresses the ways in which historic barriers to female participation in sport, and the wider social subjugation of female needs and ambitions to maleones, continued to manifest in women`s rowing throughout the second half of the twentieth century. Using a mixed methodology, juxtaposing archival sources with oral histories, it foregrounds the lived experience of a cohort of women who competed for Great Britain over this period. It makes no claim to a comprehensive account; rather, it advocates for the value of the individual, and necessarily partial, insight that characterises oral history. This thesis contributes to the growing literature pertaining to women`s sport in two important ways: firstly, as a close analysis of women`s rowing in Britain, and secondly, as a case study of the intersection of gender and sport in social history. It identifies increasing -yet, uneven -individual and collective excellence, ambition and achievement in international rowing, and argues that the alignment of personal and institutional understandings of sport was a driver of fulfilment and of success. It suggests that increased centralisation and funding, notably fromthe introduction of the National Lottery, created new and different costs to the individual, as well as opportunities.